The nucleus of Islamic religion and its bearing upon the Islamic concept of salvation and the practice of multiculturalism in contemporary Malaysia - Md. Noon, Hazizan (Centre for Interdisciplinary Study of Monotheistic Religions (CISMOR), 2007)
This paper discusses the core constituent of Islamic religion namely al-tawhid as the first level or principle of the religion and its role in defining or influencing the other layers or dimensions of Islamic religiosity. Its objectives are 1) to demonstrate an integrated Islamic approach in the study of religion and society/culture, and 2) to provide an overview of the influence of Islam in contemporary Malaysian society. To achieve these objectives, the paper first formulates an Islamic "theory" of salvation followed by a discussion of Malaysia's development strategy under the present administration. In its concluding part, the paper concludes that Islam agrees with the general contention regarding "salvation" that, "(t)he way to salvation is to live according to the laws of God." However, Islam has its own unique teachings on how to live according to the guidance and laws of Allah. The discussion provides a preliminary Islamic perspective on some issues relating to salvation and its "perceived" implications for development in multicultural Malaysia stressing on the substance and spirit of Islam which essentially means submission and peace.